Pengaruh Kompetensi dan Independensi Auditor pada Kualitas Audit - Pusparani, Ni Ketut Ayu Mirah; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 30 No 3 (2020), 2020)
Public accountants are professionally accountable to the public for the quality of their audit reports. In carrying out its duties an auditor must have the skills and experience by considering quality and quantity. The purpose of conducting research on the relationship of competence and independence in audit quality is to obtain empirical evidence of the relationship between the two. The population in this study was 82 auditors. The saturated sample technique is a technique used to determine the sample and 52 auditors who are part of the 13 KAPs registered at IAPI and made respondents in this study. Multiple linear regression analysis was chosen to analyze the data. The results prove that good auditor competence and good independence will improve the quality of audit reports produced by an auditor. Keywords: Competency; Independence; Audit Quality.